Cardiovascular CT and MR Imaging From Technique to Clinical Interpretation - Catalano, Carlo; Anzidei, Michele; Napoli, Alessandro; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
The availability and diffusion of high-performance technologies has strengthened the role of CT angiography and MR angiography as simple, reliable techniques for the characterization and treatment planning of the principal diseases of the cardiovascular system, an understanding of which has become essential for all radiologists. The aim of this book is to provide concise but thorough information and guidance on the main methods and examination techniques used when performing high-quality CT angiography and MR angiography studies in a broad range of clinical settings. The lucid text is supported by a large number of case studies and is rich in advice on image interpretation and practical suggestions for the evaluation and reporting of the examinations. Importantly, a central feature is detailed comparison of the advantages and limitations of the two techniques in various diseases and vascular regions; the book will therefore enable both trainee and expert radiologists to understand their indications and to select the most appropriate technique in different contexts.
Keywords: Medicine; Radiology, Medical; Angiography; Cardiology; Vascular Surgery; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Cardiology; Angiology; Vascular Surgery